Pharmacokinetics, safety and tolerability of ipatasertib in combination with palbociclib and fulvestrant in patients with advanced breast cancer in a phase Ib study - Cheung, Kit Wun Kathy; Arzumanova, Ksenia; Poon, Victor; Harris, Adam; Johnson, Ryan; Schimmoller, Frauke; Sane, Rucha (Frontiers in Pharmacology, 2025)
IntroductionIpatasertib is a potent, highly selective, small molecule AKT inhibitor that has been evaluated in combination with palbociclib and fulvestrant for the treatment of hormone receptor-positive (HR+) human epidermal growth factor receptor two negative (HER2-) breast cancer. Ipatasertib is a sensitive CYP3A4 substrate and is extensively metabolized to its major metabolite, M1 (G-037720). Ipatasertib is also a mild to moderate CYP3A inhibitor in vitro. Palbociclib is a weak time-dependent CYP3A inhibitor and a CYP3A substrate. Accordingly, drug-drug interaction (DDI) between ipatasertib and palbociclib is expected when the two drugs are co-administered.MethodsThe study reported herein is a Phase Ib clinical trial that aimed to evaluate the safety and pharmacokinetics (PK) of 300 mg ipatasertib in combination with palbociclib and fulvestrant (NCT04060862). The ipatasertib and M1 PK at steady state as a single agent were compared to that in combination with palbociclib and fulvestrant to evaluate the magnitude of DDI between ipatasertib and palbociclib.ResultsThe PK analysis showed that the area under the concentration-time curve from time 0–24 h at steady state (AUC0-24,ss) and the maximum observed plasma concentration at steady state (Cmax,ss) of ipatasertib increased by 68% and 49%, respectively, when ipatasertib was coadministered with palbociclib and fulvestrant compared to administration of ipatasertib alone. A similar trend was observed for M1 with AUC0-24,ss and Cmax,ss increased by 20% and 14%, respectively, when ipatasertib was coadministered with palbociclib and fulvestrant compared to administration of ipatasertib alone. Palbociclib plasma trough concentrations at steady state were generally comparable with historical data.ConclusionThis study indicated a DDI between ipatasertib and palbociclib, leading to increased ipatasertib exposure. The combination regimen of ipatasertib 300 mg with palbociclib and fulvestrant had a notable and manageable safety profile, that is generally consistent with the known risks of each individual study drugs in patients with HR + HER2-breast cancer.